Validation of a Health Characterization Model for Tilapia Farming in a Brazilian Federative Unit - Ricardo da Silva Raposo; Nádia Valesca Biral de Oliveira; Marina Karina de Veiga Cabral Delphino; Carlos Augusto Gomes Leal; Ana Lourdes Arrais de Alencar Mota; Fabiano José Ferreira de Sant’Ana (Fishes)
Brasília, Distrito Federal, is among the Brazilian cities with the highest number of tilapia farms, with around 660 farms, of which 112 are commercial. The aim of this study was to validate a health characterization model for commercial tilapia production using the production chain in the Distrito Federal (DF), one of Brazil’s 27 federative units, by applying a semi-structured questionnaire. A total of 112 farms were categorized according to the degree of vulnerability to the introduction of pathogens and the risk of dissemination using two weighted scorecard tables that evaluated 15 items each. After calculating the mean between the two variables, the farms were classified from A (insignificant risk) to D (high risk). Most of the commercial tilapia farms in the Distrito Federal were categorized as B (39; 34.8%) and C (53; 47.3%), representing low and medium risk, respectively. When comparing the different commercial groups, a significant difference (p < 0.05) was observed in the mean scores between closed-system fattening farms and both semi-closed fattening farms and pay-to-fish farms. Closed-system fattening farms, such as those using biofloc, aquaponics, and recirculation aquaculture systems, showed the lowest vulnerability to pathogen entry and the lowest risk of disease spread. The study’s findings provide valuable health information for the official veterinary service of the DF, enabling the categorization of farms, identification of production units, and determination of the most vulnerable strata. Furthermore, the model can be easily applied by private companies and by official veterinary services in other states or countries with significant tilapia production that need to implement risk-based surveillance programs for tilapia farms.